Preliminary Anti-Coxsackie Activity of Novel 1-[4-(5,6-dimethyl(H)-1H(2H)-benzotriazol-1(2)-yl)phenyl]-3-alkyl(aryl)ureas - Piras, Sandra; Corona, Paola; Ibba, Roberta; Riu, Federico; Murineddu, Gabriele; Sanna, Giuseppina; Madeddu, Silvia; Delogu, Ilenia; Loddo, Roberta; Carta, Antonio (Medicinal Chemistry, 2020)
Background: Coxsackievirus infections are associated with cases of aseptic meningitis, encephalitis, myocarditis, and some chronic disease. Methods: A series of benzo[d][1,2,3]triazol-1(2)-yl derivatives (here named benzotriazol-1(2)-yl) (4a-i, 5a-h, 6a-e, g, i, j and 7a-f, h-j) were designed, synthesized and in vitro evaluated for cytotoxicity and antiviral activity against two important human enteroviruses (HEVs) members of the Picornaviridae family [Coxsackievirus B 5 (CVB-5) and Poliovirus 1 (Sb-1)]. Results: Compounds 4c (CC50 >100 μM; EC50 = 9 μM), 5g (CC50 >100 μM; EC50 = 8 μM), and 6a (CC50 >100 μM; EC50 = 10 μM) were found active against CVB-5. With the aim of evaluating the selectivity of action of this class of compounds, a wide spectrum of RNA (positive- and negativesense), double-stranded (dsRNA) or DNA viruses were also assayed. For none of them, significant antiviral activity was determined. Conclusion: These results point towards a selective activity against CVB-5, an important human pathogen that causes both acute and chronic diseases in infants, young children, and immunocompromised patients.
Keywords: antiviral activity